The Impact of Leadership Practices on the Adoption of Digital Transformation: The Moderating Role of Organizational Culture in Jordanian Manufacturing Sector - Khalayleh, Wiam; Rohaida, Siti; Al-Khazaleh, Suhaib Mohammed (International Review of Management and Marketing, 2024)
This study investigates how organizational culture influences the relationship between leadership practices and digital transformation, as well as the impact of digital leadership practices on the adoption of digital transformation inside organizations. Using a quantitative approach, data from numerous firms reveal that achieving digital transformation necessitates effective leadership, with specific leadership components such as communication, strategic planning, digital leadership, and continuous improvement being crucial. The findings show that, depending on how effectively organizational culture fits with leadership initiatives, it can either facilitate or delay digital change. The study underlines the importance of purposeful investments in leadership development and cultural alignment for successful digital disruption management. While emphasizing the importance of cultivating an innovative culture and giving leaders with practical insights.